PENGGUNAAN METODE BERCERITA DALAM PENGEMBANGAN MORAL ANAK DI RA BAITUL JUMA’AH - Wiwik Sartika Sari; Marmawi Marmawi; Muhamad Ali (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe aim of this research  is to determine the use of telling story method in developing moral behavior to 5-6 years old children at RA Baitul Juma'ah West Pontianak. this research used qualitative approach and descriptive method. The samples are 5-6 years old children at B1 class consisted 18 children and also the teacher of B1 class. The techniques of data collection were interview, observation, documentation, and field note. While the technique of data of analysis were data collection, data reduction, data presentation and drawing conclusion or verification of data. Based on the results of data analyzed on the use of telling stoty method in developing moral behavior in 5-6 years old children in Baitul Juma'ah West Pontianak, the researcher concluded  that the the use of telling stoty method in developing moral behavior in 5-6 years old children  in Baitul Juma'ah Pontianak are effective and followed the steps to implement the telling story method, the problems faced during storytelling activities, and the media are sufficient and the activities given are related to the development of children's moral behavior. Keyword : Telling story method, Moral Behavior.